PEMETAAN GLOBAL PENELITIAN AKUNTANSI DIGITAL: ANALISIS BIBLIOMETRIK 2000–2025 PADA DATABASE SCOPUS - Judijanto, Loso (Gapenas Publisher, 2025)
This study aims to map the global development of the scientific literature in the field of digital accounting using a data-based bibliometric approach from Scopus. With the help of the VOSviewer software, an analysis of keywords, collaboration networks, and thematic trends from relevant publications over the past two decades was conducted. The visualization results show that